Investigation Nonlinear Properties (First and Second Hyperpolarizabilities) of The Nitro-thieno [3,2-b] thiophene -fullerene (C20) Molecule - Samira Resan; Mohanned Al-Anber Al-Anber (مجلة بغداد للعلوم, 2024)
In this study, nonlinear optical (NLO) properties of nitro-thieno [3,2-b] thiophene-fullerene (C20) molecule was systematically investigated using density functional theory (DFT) methods at the B3LYP level with a 6-31 + G(d,p) basis set. Fullerene (electron-donor) is associated with thieno [3,2-b] thiophene (π-conjugated bridge), forming a charge-transfer framework, and nitro is a strong electron-acceptor. The dynamic properties of the molecule, including first and second hyperpolarizability, resulting from second harmonic generation β(-2ω; ω,ω), third harmonic generation γ(– 2ω; ω, ω, ω), Pockels effect β(-ω; ω,0), and Kerr effect γ(–ω; ω, 0, 0), were investigated, which are essential evaluation indexes for creating nonlinear materials. The molecule exhibits excellent nonlinear responses, where it was found that the highest linear response of the coefficients above at the wavelength 455.6 nm. Absorption spectra reveal that these molecules have infrared transparent regions and are novel nonlinear molecules. Therefore, linking nitro-thieno[3,2-b]thiophene with fullerene (C20) efficiently designs high-performance nonlinear molecules.